Major principles in traditional cosmologies with special reference to metaphysics of ibn 'ARABI' - Norma Kassim (International Institue of Islamic Thought and Civilization, International Islamic University Malaysia, 2011)
This dissertation applied the metaphysical-cosmological ('ilm taşawwuf – 'ilm al-kawn) explanations with reference to the thoughts of Ibn 'Arabī in determining the fundamental major principles that influence and govern the cosmos. The study involved the esoteric dimension of the ontological concept of God and the cosmos, and the underlying inter-relationships of cosmos and Man with respect to God. The work on ancient and traditional cosmologies included Egyptian, Sumer-Babylonian, Iran-Zoroastrian, Hindu-Brahma, Tao, Greek-Hellenistic and Islam, with the latter acting to purify the Tawhidic principle of the various cosmologies. The discussion started with definitions on traditional cosmology and the symbols and signs embodied in the cosmic entities, which paved towards recognizing God as the origin of the cosmos and its creator. The study also established the original and eternal belief in the Absolute Divine unity within an archetype of a hierarchical cosmos, dual aspects of feminine and masculine principles, with Man (microcosm) placed into a prominent position amongst the cosmic entities (macrocosm), to manifest the full qualities of God. The explications of Ibn 'Arabī's thoughts described clearly the dual concept of the cosmos as opposed to the Oneness of God, with love and mercy as the basis of creations and existence. This study then used the cosmological-metaphysical aspects to look into the roles of men and women, in imitating the cosmic principles and establishing a polar and complementary relationship with each other, as opposed to the theories brought by feminism and post-modernism which are progressively destroying traditional religious values. This dissertation also highlights the importance of Man (al-insān al-Kāmīl), in manifesting the hidden treasure of God and his servitude to Him, which established his worth as God's vicegerent (khalīfa) on earth, aptly the reason for creations and existence